2015
DOI: 10.1016/j.dadm.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance before and after the onset of subjective cognitive decline in old age

Abstract: Background Our objectives were (1) to test the association between the report of subjective cognitive decline (SCD) and prospective objective cognitive performance in high age individuals and (2) to study the course of longitudinal cognitive performance before and after the first report of SCD. Methods Cognitively normal elderly participants of the German Study on Ageing, Cognition, and Dementia study (N = 2330) with SCD (subjective decline in memory with and without as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 49 publications
10
114
1
7
Order By: Relevance
“…Similar to previous studies, our study demonstrated that self-perceived cognitive decline was highly correlated with psychological symptoms [16, 19, 21, 4547], and informant-report of subject’s cognitive decline correlated better than self-report to objective cognitive tests [22, 23]. We used the GDS to assess depressive symptoms in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Similar to previous studies, our study demonstrated that self-perceived cognitive decline was highly correlated with psychological symptoms [16, 19, 21, 4547], and informant-report of subject’s cognitive decline correlated better than self-report to objective cognitive tests [22, 23]. We used the GDS to assess depressive symptoms in our study.…”
Section: Discussionsupporting
confidence: 81%
“…This decline from “normality” to a state with experienced cognitive difficulities only refers to the subjective experience of the individual and not to objective neuropsychological measures, which are by definition within the normal range. Nonetheless, there may be subtle decline from a prior level on objective tests, as demonstrated in studies where SCD was preceded by a subtheshold decline in immediate and delayed verbal recall (24) and by decline in psychomotor processing speed (25). This supports the idea that SCD represents the self-experience of cognitive decline before impairment becomes detectable on standardized neuropsychological tests (2, 7, 8, 24, 26).…”
Section: Resultsmentioning
confidence: 99%
“…Also normal aging is associated with SCD, however, there are a proportion of elderly individuals, who deny cognitive worsening, even on active inquiry. In a German sample of over 3327 individuals without dementia over the age of 75 (average age 80 years, AgeCoDe study), about 30% answered that they did not experience memory decline (79). Overall, the causes of SCD reporting in individuals are numerous, including age-related factors, personality traits and medical factors, one of which is early neurodegeneration.…”
Section: Resultsmentioning
confidence: 99%
“…SCD provides valuable predictive information about risk of cognitive decline (Hohman et al 2011; Snitz et al 2015) and future progression to AD dementia (Koppara et al 2015; Reisberg et al 2010; Wang et al 2004). A meta-analysis has suggested an increased annual rate of progression to MCI by 7% or AD dementia by 2% in comparison with those without SCD (Mitchell et al 2014).…”
Section: Introductionmentioning
confidence: 99%